PENGARUH KUALITAS PELAYANAN PEMBIMBING IBADAH MANASIK HAJI TERHADAP TINGKAT KEPUASAN JEMAAH - soleh, soleh; Yuliani, Yuliani; Nur Chidayah, Prita Priantini (Mabrur: Academic Journal of Hajj and Umra, 2024)
The purpose of the study was to determine the effect of the quality of service of Hajj ritual counselors on the level of satisfaction of the congregation of KBIHU Pusdai Bandung city. The theory used in this research is the theory of service quality from Tjiptono. The method used in this research is a quantitative approach, by filling out a questionnaire. The sample in this study were 78 people. The data was analyzed using the Simple Regression Analysis Technique using the help of SPSS software. The results of this study obtained a coefficient of determination of 49.5% while the remaining 50% was influenced by other factors. The results of hypothesis testing can be proven that the significance value <0.05, namely 0.000, this shows that there is a significant influence between service quality on congregation satisfaction.Keywords : Quality of mentors; Congregational satisfaction; KBIHU; Pusdai